Guidelines and recommendations of cardiovascular therapy for patients who undergo non cardiac surgery - Malinovska-Nikolovska, Liljana; Shirgoska, Biljana; Shosholcheva, Mirjana (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University in Skopje, R.N.Macedonia, 2017)
Most of the patients scheduled for non-cardiac surgery have one or more comorbidities which are treated with certain medical therapy. It is not always clear whether to continue, stop or change this therapy during the perioperative period. 2014 European Society of Cardiology (ESC) and the European Society of Anesthesiology (ESA) guidelines on cardiovascular assessment and management in noncardiac surgery came to the scene. In the same year, 2014 American College of Cardiology (ACC) and American Heart Association (AHA) Guidelines on perioperative cardiovascular evaluation and management of patients undergoing noncardiac surgery were issued, and they also represent the official position of these societies. The aim of this article is to compare and find the similarities and the differences between the two guidelines concerning perioperative medical therapy.
Водичи и препораки за кардиоваскуларна терапија на пациенти за некардијална хирургија